Analysis of Road Performance at the Center of Community Activities Due to Side Obstacles (Case Study of Alun-Alun Sukaraja) - Anisa Awaliyah; Muhamad Taufik (Fakultas Teknik Sipil dan Perencanaan, 2025)
In Sukaraja Square, congestion often occurs, as well as increasing the risk of accidents due to the absence of adequate traffic arrangements. The purpose of this paper is to analyze the road performance that occurs in the center of community activities due to side obstacles. This research uses the Indonesian Road Capacity Guidelines (PKJI) 2023 method. The survey was conducted at the Sukaraja Square intersection. The data collected included road geometry, vehicle volume and vehicle speed. For data collection in the road intersection area and the center of community activities using the method of systematic observation of vehicles in the road area. The results of this study indicate that there is no major potential hazard but the surrounding community must remain careful because the area is still with inadequate facilities.